Political Reorientation of Indonesian Sharia Economic Law: Legal Politic of Trade Law on Sharia Multilevel Marketing - Tri Hidayati; Masyithah Umar; Fathurrahman Azhari (Fakultas Syariah UINSI Samarinda, 2022)
Sharia multilevel marketing is a part of Sharia economic activity that has not been internalized in Indonesian trade law. This article discusses the formation of legal norms for direct selling in Indonesia and analyzes the legal politics of establishing trade law against sharia multilevel marketing. This article is normative legal research that uses both statutory and historical approaches. The data for this study were sourced from literature and interviews and using the inductive method analysis. The findings are, firstly, the law of multilevel marketing in Indonesia, through the stages of regulation and legislation, aims to provide legal certainty and anticipate the practice of pyramid schemes. Second, in legal politics, the formation of national trade law is not responsive to the existence of a Sharia economic system, especially sharia multilevel marketing.